A Recalculation of the Dissociation Constants of InSO4+ and the Corresponding Thermodynamic Functions - Mahaseth, Awadhesh; Jha, S.K.; Jha, S.N. (Asian Journal of Chemistry, 2010)
We have recalculated the dissociation constants of InSO4+ at 5º,15º,25º and 35ºC taking In2(SO4)3T:H2SO4T: 4:5 using improved method of computation of results. From the knowledge of dissociation constants at different temperatures, the corresponding thermodynamic parameters have also been calculated.